Identifying a 'super-responder' phenomenon in three African countries: implications for prehospital emergency care training - Eisner, ZJ; Delaney, PG; Raghavendran, K; Klapow, JC; Klapow, MC (Elsevier, 2021)
Background: Few countries in Sub-Saharan Africa have robust emergency medical services (EMS). The WHO recommends training lay first responders (LFRs) as the first step toward EMS development while Disease Control Priorities (DCP) suggests training 0.5%-1% of a population for adequate emergency catchment. After launching three LFR programs in Africa, this study investigated subsequent skill usage and conducted demographic analyses to inform future recruitment of high-responding LFRs.